ASSESSING MOTIVATION AND SATISFACTION IN AN EMERGING TYPOLOGY OF SPORTS TOURISM: PADDLE TENNIS - José Manuel Ramírez-Hurtado; Concepción Paralera-Morales (Enlightening Tourism: A Pathmaking Journal)
The present work is framed within the literature on emerging leisure activities. The goals of the present work are: (1) to identify the socio-economic characteristics of paddle tennis tourism; (2) to identify the reasons why tourists choose paddle tennis tourism; (3) to segment the paddle tennis tourism market by means of paddle tennis tourists’ motivation, sociodemographic variables and variables related to the event participants; (4) to measure the satisfaction achieved during the experience. The results of this study indicate the existence of four dimensions for the measurement of the motivation of paddle tennis tourists. The results also show the existence of three groups of tourists according to their satisfaction in practising paddle tennis tourism. The analysis of paddle tennis tourism enables their behaviour to be determined and information on the profile of this type of tourist to be ascertained, thereby allowing related companies, governments, tourism agents and managers to orientate their strategies so as to achieve considerable economic benefits.